Pengembangan E-Modul Interaktif pada Mata Kuliah Praktikum Pajak Penghasilan : Development of Interactive E-Modules in Income Tax Practicum Courses - Retta Farah Pramesti; Tantri Annisa Hanjani; Gilar Budi Pratama; Efri Elsridayani Purba (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to overcome the problem of non-standardized teaching materials and low practical skills of students in the Income Tax (PPh) Practicum course. This challenge impacts the effectiveness of learning and students' readiness to understand and apply the concept of PPh. Therefore, it is necessary to develop innovative, interactive, and relevant teaching materials to improve students' understanding of the material, learning motivation, and practical skills. The practicum module is an important thing to prepare in practicum learning as a tool that supports student learning to be more effective and efficient in understanding the existing material. This study uses the Research and Development (RnD) method with the 4D development model (Define, Design, Develop, and Disseminate). The research stages include needs analysis, interactive module design, development and limited trials on 37 students, and evaluation of the module's feasibility by experts and users. The developed e-module is feasible, with a score of 80% for content quality, learning objectives, and instructional, and 100% for the quality of interactive teaching materials. The level of student satisfaction reached 89.2%, while the quality of the questions was assessed at 91.9%, indicating the module's effectiveness in improving students' understanding, learning motivation, and practical skills. This study successfully developed an interactive-based PPh Practicum e-module, which was feasible and effective in enhancing students' knowledge, motivation, and practical skills. Further research is recommended to expand the module's implementation and integrate tax software to support students' readiness in the world of work.